Genome rearrangements activate the Epstein-Barr virus gene whose product disrupts latency. - Rooney, C (1988)
A defective Epstein-Barr virus (EBV) containing a deleted and rearranged genome (het DNA) causes latent EBV to replicate. This activity maps to the 2.7-kilobase-pair WZhet fragment. The BZLF1 open reading frame, present within WZhet as well as in the standard viral BamHI Z fragment, encodes the protein ZEBRA, which induces viral replication. Using gene transfers into Burkitt lymphoma cells, we now demonstrate that rearranged sequences juxtaposed to BZLF1 in het DNA facilitate expression of ZEBRA protein. Two stretches of EBV sequences within a palindromic region of het DNA contain positive regulatory elements. One set, derived from the viral large internal repeat, is newly positioned upstream of BZLF1; the second set is downstream of BZLF1 in het DNA. The capacity of defective HR-1 viruses to disrupt latency of the standard EBV genome is due to abnormal regulation of the BZLF1 gene as a result of genomic rearrangements.